The Importance of Expert Testimony in Proving Corruption Crimes - Ismawati Septiningsih (IJOLARES : Indonesian Journal of Law Research, 2023)
The criminal act of corruption is an extraordinary crime that has an extraordinary impact on the state and the survival of its people. Corruption as an extraordinary crime requires extraordinary handling efforts as well, especially in the process of proving it. Proving corruption often requires the role of experts from several disciplines to ensure that corruption has actually occurred. The purpose of writing this article is to analyze the existence of expert testimony as evidence in proving corruption and the extent to which expert testimony contributes to convincing judges that corruption has occurred. The writing of this article uses normative legal research methods with a statutory approach. The results of this study are that the submission of expert testimony to the trial of corruption will increase the judge's confidence in the truth of other evidence submitted by the public prosecutor, and strengthen the judge's conviction to pass a sentence of punishment if indeed from the existing evidence the defendant is legally and convincingly proven to have committed corruption.